Fruit and Non-Starchy Vegetable Acquisition and Supply in Solomon Islands: Identifying Opportunities for Improved Food System Outcomes - Farrell, Penny; Sharp, Michael; Reeve, Erica; Brewer, Tom; Farmery, Anna; Wate, Jillian Tutuo; Bogard, Jessica; Kanamoli, Samson; Thow, Anne (MDPI, 2023)
The Pacific Guidelines for Healthy Living recommend consuming a minimum of five servings of fruit and/or non-starchy vegetables each day, however, diets in Solomon Islands stray from the regional and global trend of healthy diets high in fresh fruit and vegetables. Our study drew on multiple sources of data and a food systems framework to show a country-wide picture of the role and benefits offered by fruit and non-starchy vegetables in Solomon Islands. First, we analysed data on fruit and non-starchy vegetable consumption and matched this to the data on supply. Second, we used a policy documentary analysis to highlight opportunities for the roles of fruit and non-starchy vegetables in the Solomon Island food system to advance progress in multiple Sustainable Development Goals. Key findings related to supply were the findings that domestic production of fruit and non-starchy vegetables is insufficient to meet per capita requirements, which coupled with our finding that per capita national level supply through imports is inconsequential, thus highlighting important undersupply issues for the nation. The food environment analysis indicated multiple further challenges hampering fruit and non-starchy vegetable consumption. Integrated with our analysis of policy, these revealed several opportunities, including improving affordability of this healthy commodity, enhancing livelihood equitability of supply chains, and strengthening environmentally sustainable agricultural practices that support increased production.